TVC Experiment 2018/19: TerraSAR-X backscatter data ... - Montpetit, Benoit; Wendleder, Anna; King, Joshua; Toose, Peter; Derksen, Chris; Brady, Mike (Zenodo, 2024)
This dataset contains the processed, backscatter data from TerraSAR-X (TSX) satellite data, as part of Environment and Climate Change Canada's 2018-2019 Trail Valley Creek Snow Experiment (TVC Experiment 18/19). These TSX data were collected and processed to evaluate against a network of Steven’s HydraProbe soil monitoring sensors, and coincident in situ snowpit measurements, airborne radar, and other satellite radar data to better understand soil-snow-radar interactions in a tundra environment. The TSX data was ordered to provide a wintertime series of repeat overpasses from September 2018 to June 2019, over the Trail Valley Creek research station (https://www.trailvalleycreek.ca/) in Northwest Territories, Canada. Three periods of in situ snow measurement took place in November 2018, January 2019, and March 2019. TSX data was acquired from two stripmap orbits, one in HH/HV and the other in VV/VH. The TSX products were processed using the European Space Agency’s (ESA), Sentinel Application Platform (SNAP) ... : The TerraSAR-X data are available through the DLR (© DLR 2019). ...